Direct cleavage of human TATA-binding protein by poliovirus protease 3C in vivo and in vitro. - Clark, M E (Mol Cell Biol, 1993)
Host cell RNA polymerase II (Pol II)-mediated transcription is inhibited by poliovirus infection. This inhibition is correlated to a specific decrease in the activity of a chromatographic fraction which contains the transcription factor TFIID. To investigate the mechanism by which poliovirus infection results in a decrease of TFIID activity, we have analyzed a component of TFIID, the TATA-binding protein (TBP). Using Western immunoblot analysis, we show that TBP is cleaved in poliovirus-infected cells at the same time postinfection as when Pol II transcription is inhibited. Further, we show that one of the cleaved forms of TBP can be reproduced in vitro by incubating TBP with cloned, purified poliovirus encoded protease 3C. Protease 3C is a poliovirus-encoded protease that specifically cleaves glutamine-glycine bonds in the viral polyprotein. The cleavage of TBP by protease 3C occurs directly. Finally, incubation of an uninfected cell-derived TBP-containing fraction (TFIID) with protease 3C results in significant inhibition of Pol II-mediated transcription in vitro. These results demonstrate that a cellular transcription factor can be directly cleaved both in vitro and in vivo by a viral protease and suggest a role of the poliovirus proteinase 3C in host cell Pol II-mediated transcription shutoff. IMAGES: